Potential association of certain microRNA gene polymorphisms with recurrent pregnancy loss susceptibility in Saudi women - Aya Rabaa; Afrah Alkuriji; Aishah Kabbi; Samiah Almalki; Zainab Almasawi; Maha Daghestani; Hana Hakami; Jawaher Alzahrani (PLoS ONE, 2025)
MicroRNA (miRNA) polymorphisms are increasingly recognized as important regulators of reproductive outcomes, but their role in recurrent pregnancy loss (RPL) is still unexplored in specific populations. This case control study investigated six miRNA polymorphisms (miR-10-A > T, miR-125-G > A, miR-146a-C > G, miR-149-T > C, miR-323b-C > T, miR-499-A > G) in 50 Saudi women with idiopathic (≥ 2 losses) and 50 matched controls (≥ 1 live birth, no loss history) using PCR Sanger sequencing. Significant associations were found for heterozygous genotypes of miR-146a-C > G (OR=2.29, 95% Cl:1.02–5.18, *p* = 0.046) and miR-149-T > C (OR=2.67, 95% Cl:1.08–6.61, *p* = 0.034) with higher prevalence in RPL patients versus controls, while other polymorphisms showed no significant association (*p* > 0.05). These results suggest miR-146a and miR-149 can contribute to RPL susceptibility in Saudi women, highlighting their potential as population-specific genetic biomarkers and underscoring the need for further research into miRNA-mediated pregnancy maintenance mechanisms.